Moss diversity in Malesia: a literature review (Research, Society and Development, 2020)
This article has the objective to overview literature on the topic of the distribution of Malesia mosses which is closely related to tropical forest. This diversity and distribution is an important concern because of the increasing rate of destruction of tropical forests throughout region. Using theoretical literature method, the author summarizes mosses’ wide geographical distribution covering the tropical regions of Asia, the Pacific and Australia. Some types of liverworts do not spread west across the Wallace line. A review of liverworts literature has been conducted but a review specifically on the moss diversity in Melasia region is limited. Thus, this review includes a brief introduction to mosses and then focuses on the following topics; the characteristics of mosses; development of moss plants; classification of moss plants; benefits of moss plants and moss diversity in the Malesia region.